How does greater bank competition affect borrower screening? Evidence from China's WTO entry - Chemmanur, Thomas J.; Qin, Jiaqi; Sun, Yan; Yu, Qianqian; Zheng, Xiang (Journal of Corporate Finance, 2020)
We analyze the relationship between greater bank competition and the screening of potential borrowers. Using a large sample of Chinese private firms and China's entry into the WTO as a unique setting leading to greater bank competition, we find the following. First, the sensitivity of bank credit to prior borrowing-firm performance increases after China's WTO entry. This sensitivity increase is greater in more bank-dependent industries and smaller in Chinese regions with greater financial sector development. Second, the increase in the sensitivity of bank credit to firm performance is much greater for state-owned firms compared to private firms. Third, the effect of bank credit on subsequent firm productivity and performance is greater for loans given after China's WTO entry compared to those given prior to WTO entry. Overall, the results of our empirical analysis suggest that the stringency of bank screening of borrowers in China increased with greater banking sector competition.